Immobilization of Antimicrobial Silver and Antioxidant Flavonoid as a Coating for Wound Dressing Materials - Tran HA (Dove Medical Press, 2019)
Hien A Tran,1–4 Khanh L Ly,4 Kate E Fox,5 Phong A Tran,1–3 Thi-Hiep Nguyen4 1Queensland University of Technology (QUT), Brisbane, Queensland 4001, Australia; 2Interface Science and Materials Engineering Group, School of Chemistry, Physics and Mechanical Engineering, QUT, Brisbane, Queensland, Australia; 3Centre in Regenerative Medicine, QUT, Brisbane, Queensland, Australia; 4Department of Biomedical Engineering, International University, Vietnam National University- Ho Chi Minh City (VNU-HCM), Ho Chi Minh City 70000, Vietnam; 5School of Engineering, Centre for Additive Manufacturing, RMIT University, Melbourne, VIC 3001, AustraliaCorrespondence: Phong A TranQueensland University of Technology (QUT), Brisbane, Queensland 4001, AustraliaTel +61 7 3138 6452Email phong.tran@qut.edu.auThi-Hiep NguyenDepartment of Biomedical Engineering, International University, Vietnam National University- Ho Chi Minh City (VNU-HCM), Ho Chi Minh City 70000, VietnamTel +84 2837 244 270Email nthiep@hcmiu.edu.vnPurpose: The aim of this study is to develop a new coating for wound dressings that is comprised of antimicrobial silver (Ag) and antioxidant flavonoid quercetin (Q).Methods: Dip-coating was used to apply the coating on cotton gauge as a model dressing. Ag was immobilised using polydopamine as a priming and catalytic layer followed by coating of quercetin that was incorporated in a functionalized polydimethylsiloxane. The coating was investigated using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and release assay. The antimicrobial activity of quercetin and Ag was tested against Staphylococcus aureus (S. aureus). A surgical wound model on mice was used to evaluate the effects of the coated dressing on wound healing rates and tissue histology.Results: Ag and quercetin showed enhanced antimicrobial activity against S. aureus when used in combination. Ag and quercetin were successfully immobilized onto the fibre of the dressing using the dip-coating process. The coating released Ag and quercetin over 8 days and showed strong antioxidant activity. In the wound healing model, complete wound closure was achieved in 12 days in the group receiving coated dressing and was associated with an enhancement in tissue remodelling and neo-angiogenesis and the reduction in tissue inflammation.Conclusion: These new antimicrobial-antioxidant coatings may be promising in the development of advanced wound care therapies.Keywords: quercetin, Ag, antioxidant, antibacterial, wound healing